Agricultural development and economic growth - Southworth, Herman M.; Johnston, Bruce F. (Ithaca, N.Y. : Cornell University Press, 1967)
This book examines issues, problems and complexities of agricultural development and economic growth. It is a collection of fourteen papers written by eighteen scholars who have distinguished themselves in their respective fields. Each paper has been commented upon by one or two equally reputed scholars. The author of each paper gives a critical survey of the literature on the subject and provides an extensive bibliography at the end of the paper. The topics surveyed are: agricultural development, barriers to change, infrastructure, education and training for agricultural growth, farm size and agricultural productivity, land reform, food and nutrition, marketing institutions, export of agricultural products, agricultural taxation, agricultural price policy, and programming of agricultural development.
"First published 1967."
Includes bibliographical references and index.
lje 26/01/2018
Loans
Keywords: Agriculture--Economic aspects; Agriculture; Developing countries